2014
DOI: 10.1097/bot.0000000000000052
|View full text |Cite
|
Sign up to set email alerts
|

Ankle Radiographs in the Early Postoperative Period

Abstract: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 4 publications
1
25
0
Order By: Relevance
“…Since patients were exposed to unnecessary radiation, we believe that imaging could be delayed to a later follow-up visits in which fracture-healing needs to be assessed. We agree with the previous findings that early postoperative radiographs may not be beneficial in all ankle fracture patients, but radiographs may be indicated if the clinical picture necessitates them [3].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Since patients were exposed to unnecessary radiation, we believe that imaging could be delayed to a later follow-up visits in which fracture-healing needs to be assessed. We agree with the previous findings that early postoperative radiographs may not be beneficial in all ankle fracture patients, but radiographs may be indicated if the clinical picture necessitates them [3].…”
Section: Discussionsupporting
confidence: 92%
“…Early recognition of these infections is highly important because in cases with delayed diagnosis the presence of biofilm presents a highly demanding challenge for bacterial eradication and infection treatment [16,17]. A recent study with 1411 ankle fractures observed that 6.6% of ankle fracture patients had an early complication [3]. Our study showed that every tenth operatively treated ankle fracture patient required a change in treatment plan by the time of the first outpatient visit, and that 91% of the changes were exclusively due to clinical findings such as infection or cast-related issues.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations